Nanocolloids for Nanomedicine and Drug Delivery - Stefano Leporatti (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
This Special Issue highlights novel nanocolloids like magnetic nanoparticles, nanomicelles, nanoliposomes, nanocapsules, and nanoclays, stimulating novel interests and ideas in research groups involved in the development of novel nanotools within the different areas of nanomaterials. The publication of original articles contributes to scientific progress in the area of personalized medicine and further stimulates the entering into clinical praxis of such new nanosystems.